PEMANFAATAN LIMBAH TONGKOL JAGUNG UNTUK PEMBUATAN PRODUK PUPUK BIOCHAR HYBRID KAYA NUTRISI MAKRO N, P, K, S. - P., I Gusti Bagus Sugiantara D.; Jurnal Wicara; Diraksa, Mazhari Seneng; Fauzan, Muhammad; Nabilah, Ailsa; Darmayanti, Cokorda Istri Wulan; Oktaviani, Oktaviani; Rahmiati, Riry; Cahyadi, M. Bagus; Hayyi, Najma Auliya Maharani; Khairunnisa, Baiq Asya Faras; Wulan, Ir. R. Sri Tejo (Jurnal Wicara, 2025)
Agricultural land in Akar-Akar Village is dominated by dry soil with low productivity, which has become a major challenge for local farmers. On the other hand, corn cobs, which are abundantly available as post-harvest waste, have not been utilized optimally and are often considered as trash. This Community Service Program (KKN) aims to enhance the knowledge and skills of farmers in Akar-Akar Village regarding the potential use of corn cobs as biochar to improve soil quality. The method applied is a participatory approach through socialization and practical demonstration. The socialization stage provides theoretical understanding of the benefits of biochar, while the demonstration stage practices the direct process of producing biochar using a simple pyrolysis method with single drum kiln technology. The results of this activity indicate a significant increase in the community’s understanding and awareness of the benefits of biochar in improving the physical, chemical, and biological properties of soil, as well as their ability to independently produce biochar from local agricultural waste. The conclusion of this program is that the socialization and demonstration of corn cob biochar technology successfully introduced a low-cost, environmentally friendly, and sustainable solution to address the issue of dry soil fertility, while simultaneously transforming waste into a valuable resource in Akar-Akar Village.